Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

quadratic equation.

Asked by khushal305 9th September 2009, 8:41 PM
Answered by Expert
Answer:

abx2 = (a+b)2(x-1)

A = (a+b)2

abx2 = A(x-1)

abx2 - Ax + A = 0

x = [A ± (A2 - 4abA)]/2ab

{ A2 - 4abA = A(A - 4ab) = (a+b)2((a+b)2 - 4ab) = (a+b)2(a2 + 2ab + b2 - 4ab) = (a+b)2(a-b)2 }

x = [A ± (A2 - 4abA)]/2ab

x =  [(a+b)2 ±  (a+b)(a-b)]/2ab

x = (a+b) [a+b ± (a-b)]/2ab

x = {(a+b)/b, (a+b)/a}

Regards,

Team,

TopperLearning.

Answered by Expert 9th September 2009, 10:31 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!